Numerical Analysis of Anisotropic Influence of Mode-I Fracture Toughness under Dynamic Loading for Rock using GPGPU-based Three-Dimensional Combined Finite-Discrete Element Method (FDEM). Issue 3 (October 2021) - Min, G.J.; Fukuda, D.; Oh, S.W.; Nara, Y.; Liu, H.; Cho, S.H.
Abstract: The anisotropic characteristics of rock are responsible for diverse and difficult-to-predict crack propagation and fracturing behaviors that manifest under various loading-rate conditions. In granitic rock, anisotropy makes predicting Mode I fracture toughness under different loading-rate conditions across all three orthogonal planes difficult. The reality compounds this difficulty that anisotropy is extremely difficult to quantify experimentally, and it has proven challenging to model this fracturing process (i.e., crack initiation and propagation) and its associated stress distribution. Accordingly, no in-depth model of the underlying fracture process for anisotropic rocks under quasi-static and dynamic loading conditions exists to date. An accurate simulation capable of describing the fracture process is necessary to close this gap. We successfully simulated the dynamic fracture process using a Finite-Discrete Element Method (FDEM) along with the New Self-Consistent Scheme. A Mode I fracture toughness test for an SNDB granite specimen under quasi-static and dynamic loading conditions was simulated using a GPGPU-based 3D combined FDEM and compared Mode I fracture toughness and behavior. We discuss the effect of anisotropic characteristics and loading-rate dependency on crack propagation.